Molecular Characteristics and Distribution of Adult Human Corneal Immune Cell Types - Li, Yanxiu; Li, Haibo; Xia, Xiaobo (Frontiers in Immunology, 2022)
Background The limbus is located at a 2-mm-wide area between the bulbar conjunctiva and the cornea and has been suggested to be the niche of corneal epithelial stem cells and immune cells. Like the skin and intestines, the cornea is also an important mucosal surface, and immune cells on the cornea play critical roles in immune surveillance to ensure barrier surface homeostasis and protection from various environmental damage and infections. Single-cell RNA sequencing (scRNA-seq) analysis of protein tyrosine phosphatase receptor type C positive (PTPRC+) hematopoietic cells from the corneal limbus could provide a single cell atlas of all the immune cell subsets. Methods We performed single-cell RNA sequencing to generate transcriptomic profile for 804 sort-purified hematopoietic cells from the corneal limbus of three healthy donors. Results Our analysis identified a primary transcriptomic pattern for multiple immune cell subtypes, including naive T cells, antiviral effector CD8+ T cells, and innate immune cells such as IDO1+ mature regulatory dendritic cells (mregDCs), macrophages, monocytes, and basophils in the human corneal limbus. Conclusion Overall, single-cell transcriptomic analysis of limbal immune cells suggested the possible contribution of these cells on the adaptive and innate immune response of the human cornea.